2021
DOI: 10.1186/s12933-021-01419-y
|View full text |Cite
|
Sign up to set email alerts
|

Plasma metabolomic profiling in subclinical atherosclerosis: the Diabetes Heart Study

Abstract: Background Incidence rates of cardiovascular disease (CVD) are increasing, partly driven by the diabetes epidemic. Novel prediction tools and modifiable treatment targets are needed to enhance risk assessment and management. Plasma metabolite associations with subclinical atherosclerosis were investigated in the Diabetes Heart Study (DHS), a cohort enriched for type 2 diabetes (T2D). Methods The analysis included 700 DHS participants, 438 African A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
14
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 29 publications
(16 citation statements)
references
References 74 publications
1
14
0
1
Order By: Relevance
“…Chevli etc. [ 39 ] found fatty acid, androgenic steroids and other sub-pathways were associated with subclinical atherosclerosis in a family-based diabetes-enriched population and the associations vary in African and European Americans. Moreover, in studies on the general population, various chemical compounds of lysophosphatidylcholine have been frequently reported to be associated with atherosclerosis [ 40 , 41 ].…”
Section: Discussionmentioning
confidence: 99%
“…Chevli etc. [ 39 ] found fatty acid, androgenic steroids and other sub-pathways were associated with subclinical atherosclerosis in a family-based diabetes-enriched population and the associations vary in African and European Americans. Moreover, in studies on the general population, various chemical compounds of lysophosphatidylcholine have been frequently reported to be associated with atherosclerosis [ 40 , 41 ].…”
Section: Discussionmentioning
confidence: 99%
“…It was consistent with recent studies that increased levels of 2-(dimethylamino) guanosine and β-pseudouridine levels were related to incident heart failure and LV remodeling [ 45 , 46 ]. Furthermore, 2-(dimethylamino) guanosine has been linked to increased risk of coronary artery calcium [ 47 ] and all-cause mortality in diabetes [ 48 ], and elevated circulating levels of β-pseudouridine were associated with atrial fibrillation [ 49 ], heart failure [ 50 ] and CAD [ 51 ]. Here we report for the first time that β-pseudouridine was also a metabolic marker for the risks of death and MACE in CAD.…”
Section: Discussionmentioning
confidence: 99%
“…KEGG analysis revealed that six DEPs were enriched in the BCAA degradation pathway. Growing evidence suggests that BCAA degradation abnormalities and BCAA accumulation are important pathogenic mediators in the development of cardiovascular and metabolic diseases, including arteriosclerosis, coronary heart disease, hypertension, dilated cardiomyopathy, heart failure, and diabetes [ 26 30 ]. However, there have been no studies on SGLT2i and BCAA metabolism in the cardiovascular field.…”
Section: Discussionmentioning
confidence: 99%